2021
DOI: 10.3390/jmse9040375
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Drivers behind the Structure and Diversity of Fish Assemblages Associated with Rocky Shores in the Galapagos Archipelago

Abstract: Oceanic islands harbor unique yet fragile marine ecosystems that require evidence-based environmental management. Among these islands, the Galapagos archipelago is well known for its fish diversity, but the factors that structure communities within and between its islands remain poorly understood. In this study, water quality, physical habitats and geographical distance were assessed as potential predictors for the diversity and structure of fish assemblages. Differences in the structure of fish assemblages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Both environmental and anthropogenic factors influence the fish distribution, abundance, and diversity 33 , 40 . All sampling sites are affected by anthropogenic influences due to fishing and tourist grounds on this region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both environmental and anthropogenic factors influence the fish distribution, abundance, and diversity 33 , 40 . All sampling sites are affected by anthropogenic influences due to fishing and tourist grounds on this region.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the strong seasonality observed during the sampling years, with the average sea temperatures reaching differences of 6 °C between the warm and cold seasons, no temporal variation was detected in the diversity patterns and community structure of fish at any site. Several studies have demonstrated the influence of sea temperature on diversity patterns in fish communities 25 , 33 , 34 , 40 , 87 . However, our results show that fish communities in the coastal habitats within a region of the Galapagos Islands have a high environmental tolerance, which allows them to persist in their habitat despite drastic seasonal changes in sea temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there are no records of this species in the Galapagos in the databases of major global aggregators of location records of fishes (GBIF 2021; OBIS 2021; FishNet 2 2021). Finally, more recent observations of reef fishes at widely distributed sites in the Galapagos by experienced observers also failed to record L. inermis but did include all five common species mentioned above (Edgar 2011;Llerena-Martillo 2018;Fierro-Arcos et al 2021;Bruneel et al 2021; see also Zimmerhackle et al 2015). The only indications of the occurrence of L. inermis at those islands other than Wellington's (1975) report is the IUCN Red List assessment of this species (Rojas et al 2010), which shows it present in the northern Galapagos.…”
Section: Introductionmentioning
confidence: 99%
“…This special edition is intended to be a contribution to the knowledge of several aspects of fish biology and ecology: coastal fish diversity, coastal fisheries and commercial species, biological invasions process and non-indigenous species, interactions between fish and their environment, ethology, bioaccumulation and reproduction [1][2][3][4][5][6][7][8][9][10][11][12]. I hope this special issue will be helpful for all marine biologists involved in studies on fish biology and ecology.…”
mentioning
confidence: 99%